Atmospheric PAHs, NPAHs, and OPAHs at an urban, mountainous, and marine sites in Northern China: Molecular composition, sources, and ageing. (January 2018) - Zhang, Junmei; Yang, Lingxiao; Mellouki, Abdelwahid; Chen, Jianmin; Chen, Xiangfeng; Gao, Ying; Jiang, Pan; Li, Yanyan; Yu, Hao; Wang, Wenxing
Abstract: 18 gaseous and particulate polycyclic aromatic hydrocarbons (PAHs), 16 nitro-derivative (NPAHs), and 7 oxy-derivative (OPAHs) were analyzed by Gas Chromatography-Mass Spectrometry (GC-MS) at three locations in Northern China, an urban site (Jinan), a marine site (Tuoji island), and a mountain site (Mt. Tai). The combined gas and particulate concentrations of 18 PAHs, 16 NPAHs, and 7 OPAHs were highest at the urban site (305.91, 2.80, and 9.05 ng/m 3, respectively) and lowest at the mountain location (37.83, 0.27, and 1.59 ng/m 3, respectively). A noticeable increase in the high molecular weight PAHs was observed during polluted conditions compared to clean conditions. Diagnostic ratios clearly demonstrated that coal/biomass combustion was the major PAH source in Northern China. The particulate PAHs were the most aged at the mountain site due to long-distance atmospheric transport. The formation rate of NPAHs was most efficient at the mountain location and during heavily polluted days at the urban and marine sites. In addition, the main formation pathway for NPAHs was through the OH initiated secondary reaction. NO3 radicals most significantly contributed to the NPAHs formation at night, during clear weather, and at the mountain site. The logKp value was lowest at the urban site for most individual compounds and highest at the mountain site. Higher logKp was found for NPAHs and OPAHs compared with their corresponding parent PAHs. The linear regression of logKp vs logPL 0 at the three sites suggested that the gas-particle partitioning of PAHs might be in non-equilibrium. Graphical abstract: Highlights: Gaseous and particulate NPAHs and OPAHs were analyzed at three distinct sites. The secondary formation of NPAHs exhibited the greatest contribution at MT. The polluted days promoted the accumulation of high molecular weight PAHs and NPAHs. The logKp values for PAHs, NPAHs and OPAHs were lowest at JN and highest at MT.